2008
DOI: 10.1590/s0004-282x2008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors among elderly Brazilians over eighty with ischemic stroke

Abstract: -Introduction: An ischemic stroke is usually a catastrophic event, mostly in the elderly. Cardiovascular involvement is the leading cause of ischemic stroke in this age population and hence the knowledge about its risk factors is important for the definition of specific policies of prevention. Purpose: To evaluate the prevalence of cardiovascular risk factors in patients with age equal to or above 80 in a hospital population with ischemic stroke. Method: Retrospective study of consecutive patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…2,4,5 The sample of this study had a greater number of males over 50 years of age, in agreement with reports found in literature, which correlate cardiovascular alterations to the aging process and the occurrence of stroke. 6,7,8,9 Recent data from the United States also show a prevalence of stroke in men, but this relationship is reversed with advancing age, when women above 85 years of age present a higher risk of stroke. 10 A systematic review of 2009, which compared the differences in stroke epidemiology between men and women, observed a mean age of stroke in 68-year-old men and 72-yearold women, in agreement with this study, which showed a higher incidence among men of age over 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 The sample of this study had a greater number of males over 50 years of age, in agreement with reports found in literature, which correlate cardiovascular alterations to the aging process and the occurrence of stroke. 6,7,8,9 Recent data from the United States also show a prevalence of stroke in men, but this relationship is reversed with advancing age, when women above 85 years of age present a higher risk of stroke. 10 A systematic review of 2009, which compared the differences in stroke epidemiology between men and women, observed a mean age of stroke in 68-year-old men and 72-yearold women, in agreement with this study, which showed a higher incidence among men of age over 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…the rising incidence of aF has been recognized as a serious public health problem worldwide (table 1). [1][2][3][4][5][6][7][8][9] aF is most prevalent in the elderly (>65 years of age), who represent a large proportion of the population in the developed world. aging of the population means that health professionals, including cardiac rhythm specialists, envisage that an aF epidemic will be an upcoming challenge.…”
mentioning
confidence: 99%